Peran Guru PPKN Dalam Pengembangan Gaya Belajar Auditori Untuk Merangsang Pola Pikir Peserta Didik : (Studi Kasus Di SMP PGRI 6 Malang) - Didik Iswahyudi; Romadhon Romadhon; Maria Yovita Mau (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The auditory learning style can help students rely on their hearing. This means being able to remember and understand certain information in learning. Students need the teacher's role in developing an auditory learning style that can help students improve their learning. The aim of the research is to determine the role of PPKn teachers in developing an auditory learning style to stimulate students' thinking patterns. This research uses a qualitative case study method. data from research findings shows that the implementation of learning using the auditory learning style of students has a systematic implementation of learning as usual, namely: 1). Providing or explaining the material to be discussed using an auditory learning style or lecture method, 2). Assignments and assessments. In implementing learning using the auditory learning style, a diverse learning atmosphere is created, 3). Learning uses an auditory learning style because it is considered fun and exciting. Based on research results, the auditory learning style really helps students in carrying out the learning process in the classroom. Civics teachers play an important role in the process of developing an auditory learning style in stimulating students' thinking patterns.